The Influence of Employer Branding on Millennials' Interest in Applying for Jobs in Private Companies - Hendrawati Hamid (PT. Hafasy Dwi Nawasena, 2025)
This study aims to analyze the influence of employer branding on the interest of millennial generation in applying for jobs in private companies. In an increasingly competitive job market, companies need to create a positive image to attract the interest of millennials, who tend to prefer companies with a good reputation and values ​​aligned with their personal aspirations. This study uses a quantitative approach with a cross-sectional survey design. A questionnaire was distributed online to 100 respondents in Medan, measuring two variables: employer branding (independent variable) and the interest to apply for jobs (dependent variable). The results show that employer branding has a significant influence on millennials' interest, with a regression coefficient of 0.725 and a p-value of 0.000, indicating that factors such as company reputation, holistic well-being, self-development opportunities, and work-life balance significantly affect millennials' decisions to apply for jobs. This study also finds that social media plays an important role in introducing a company's image and enhancing its attractiveness in the eyes of millennials. Therefore, companies that can communicate positive values ​​and make good use of social media will be more successful in attracting millennial talent.